If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4w + -5) + -1(w + 7) = 0 Reorder the terms: (-5 + 4w) + -1(w + 7) = 0 Remove parenthesis around (-5 + 4w) -5 + 4w + -1(w + 7) = 0 Reorder the terms: -5 + 4w + -1(7 + w) = 0 -5 + 4w + (7 * -1 + w * -1) = 0 -5 + 4w + (-7 + -1w) = 0 Reorder the terms: -5 + -7 + 4w + -1w = 0 Combine like terms: -5 + -7 = -12 -12 + 4w + -1w = 0 Combine like terms: 4w + -1w = 3w -12 + 3w = 0 Solving -12 + 3w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 3w = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 3w = 0 + 12 3w = 0 + 12 Combine like terms: 0 + 12 = 12 3w = 12 Divide each side by '3'. w = 4 Simplifying w = 4
| 3x^2-53x+120=0 | | 2x^2+13x+14=0 | | 2y=.6(2y*y) | | y+z+6cy+6cz= | | 7x-10x=-9-12 | | M/2 | | 7x+2=5x-11 | | -20x^5+18x^4+18x^3= | | 4log(5)= | | 12x^2+39x-156=0 | | 39+(-19)+(-23)= | | 7+3s-5=8s+6 | | 9y^3-4y-45y^2+20=0 | | x*2+5x-14=0 | | (2x-3)/2 | | 8b=-10+9b | | 15%=32.50 | | 4x+x=225 | | 5t+15-6= | | t-8=10-t | | (8x^6w^3-2xw^8)/(2xw^3) | | 1/8=2/x | | x^2+1=1-2x | | F(X)=9X+3 | | 3-z=6 | | 7-3x=31-11x | | 14-6-3+3= | | -8.61-(-8.61)= | | -10-3t=-t | | 9x^2-30x-144=0 | | 36x^2y^2-6xy^3=0 | | X+x-4=148 |